The PENGARUH PEMERIKSAAN PAJAK, SANKSI PERPAJAKAN, SISTEM PERPAJAKAN, TEKNOLOGI DAN INFORMASI PERPAJAKAN - Windi Julianti; R. Septian Armel; Siti Rodiah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
Tax evasion is a serious form of violation because it can hinder state revenue and create inequality between taxpayers. The purpose of this study is to determine the effect of tax audits, tax sanctions, tax systems, and tax technology and information on tax evasion practices. This study was conducted on corporate taxpayers registered at the Bangkinang Pratama Tax Office, using a quantitative approach and survey method. Data were collected from 100 respondents with a questionnaire and analyzed using multiple linear regression through SPSS version 23. The results show that strict tax audits and sanctions have a negative effect on evasion, meaning that the higher the audit and sanctions, the practice of evasion tends to decrease. Meanwhile, the tax system and information technology have a positive effect, indicating that systems and technologies that are not yet optimal can provide opportunities for perpetrators to commit evasion.